Information systems requirements (Determination and analysis) - Donald Flynn (McGraw-Hill, 1998)
The book provides an introduction to the area of information systems, focusing on the early stages of systems development. It covers the object-oriented approach and the movement to standardization of systems development methods, the information system success and failure. It discusses also the organization and social contexts within which information systems and the power and critical systems thinking